Analisis Efisiensi Usahatani Padi dengan Sistem Alsintan Combine Harvester pada Proses Pemanenan di Desa Bareng Kecamatan Ngasem Kabupaten Bojonegoro - Septiyana, Eka Elsha; Widayanti, Sri; Tondang, Ika Sari (Universitas Galuh, 2025)
Rice harvesting is an activity aimed at obtaining rice grains from the planting process over a certain period until the crop reaches a specified level of maturity. During harvesting, the use of a combine harvester is highly recommended, as it not only increases harvesting efficiency and minimizes grain loss, but also expands the harvest area and improves the agroecosystem conditions. The purpose of this study is to analyze various factors in rice production and the technical and economic efficiency of using combine harvesters compared to traditional methods (non-combine harvester) in the rice harvesting process. The research was conducted in Bareng Village, Ngasem District, Bojonegoro Regency, using a quantitative method. The sample consisted of 100 farmers, 50 of whom used combine harvesters and 50 who did not. The results showed that farmers who used combine harvesters significantly increased both technical and economic efficiency compared to traditional methods. The largest influences on production were land size, pesticide use, and the number of workers. The R/C ratio indicated higher economic efficiency among farmers using combine harvesters, with an R/C ratio of 2.22 compared to 1.65 for traditional methods. The findings of this study prove that the use of modern technology, such as combine harvesters, can increase productivity and profitability for farmers.